Case Report: Clinical Treatment of the First Critical Patient With Coronavirus Disease (COVID-19) in Liaocheng, Shandong Province - Tian, Hui; Sui, Yuanda; Tian, Suochen; Zou, Xiuli; Xu, Zhiping; He, Huang; Wu, Tiejun (Frontiers in Medicine, 2020)
】This paper reports the clinical characteristics and diagnosis and the treatment process of the first critical COVID-19 patient in Liaocheng City who was admitted to the fever intensive isolation ward of Liaocheng People's Hospital on February 11, 2020. On admission, the patient had difficulty breathing， the oxygenation index(OI) was 135mmHg and the blood lactate (Lac) was 5.6mmol/L. After the comprehensive treatment of high-flow nasal cannula（HFNC）oxygen therapy, plasma exchange, antiviral and anti-infection therapies, immune regulating,liquid volume management, glucocorticoid, enteral nutrition support, analgesia and sedation,blood glucose control, anticoagulation and thrombus prevention, and electrolyte balance maintenance, the patient finally was cured and discharged. The purpose of the report of the treatment process is to provide some references for the clinical diagnosis and treatment of critical COVID-19 patients.